Are Emerging Market Countries Learning to Float? - Hakura, Dalia (IMF Working Papers; Working Paper ;, 2005)
The paper finds that exchange rate flexibility in emerging market countries has increased over the past decade. This "learning to float" appears to have involved a strengthening of monetary and financial policy frameworks aimed at directly addressing the key vulnerabilities that give rise to the "fear of floating." The results in the paper suggest that the trend toward greater exchange rate flexibility, alongside a strengthening of banking supervision, has afforded emerging market countries more monetary policy independence.